Debate on the relationship between Helicobacter pylori infection and inflammatory bowel disease: a bibliometric analysis - Wang, Ziye; Zhao, Shiqing; Zhong, Xiaotian; Su, Yi; Song, Yahan; Li, Jun; Shi, Yanyan (Frontiers in Microbiology, 2024)
BackgroundInflammatory bowel diseases (IBD) are chronic inflammation conditions affecting the gastrointestinal tract. Studies point out an association between Helicobacter pylori (H. pylori) infection and IBD. This study aims to visually assess the research trends and hotspots in the field of H. pylori infection and IBD, review mainstream perspectives in this field, and provide a foundation for future research and treatment.MethodsWe searched the Web of Science Core Collection Database for literature related to H. pylori and IBD, using VOS viewer to generate visual charts.ResultsA total of 246 publications were included, with articles being the predominant type of document. A significant increase in the number of publications was observed after 2011. China contributed the most of researches. Keyword clusters revealed that the researches primarily focused on immune mechanism, gut microbiome, diagnosis and treatment of IBD. Time trend results indicated that current researches centered on gut microbiota and immune mechanisms.ConclusionH. pylori infection may have a protective effect on IBD. The exact mechanisms remain unclear and may involve immunomodulation and changes of gut microbiota. Further researches are necessary for better understanding this relationship and its implications for clinical practice. Further researches and clinical practice should pay attention to this topic.